2023
DOI: 10.3389/fpls.2023.1071346
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free supernatant of Devosia sp. (strain SL43) mitigates the adverse effects of salt stress on soybean (Glycine max L.) seed vigor index

Abstract: Soil salinity is a major constraint for soybean production worldwide, and the exploitation of plant growth-promoting bacteria (PGPB) and their bioactive metabolite(s) can improve plant salinity tolerance. With this objective, two experiments were performed, aiming to test 4 culture media (YEM(A), TYE(A), TS(A), and LB(A)) for growing a novel Devosia sp. (strain SL43), and then evaluating cell-free supernatants (CFS) from the Devosia sp. on germination of soybean (Glycine max L.) seeds under salinity stress. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The relative abundance of Devosia, another Gram− bacterium, was also increased in the HM samples, with members of this taxon known to tolerate brackish conditions [70]. Devosia can be associated with green algae which is consistent with its increased abundance as the chl a levels increased 3.4-fold, serving as a diazotroph by fixing nitrogen, but it can also facilitate the maintenance of ion homeostasis, which may be significant in the mixed salts of the "eco-friendly" de-icer [71,72]. Since members of Devosia can be halophilic and this genus was found at the highest relative abundance in the HM samples, we cannot exclude that it too was a contaminant in the M de-icer formulation.…”
Section: Shifts In Microbiota At High Concentrations Of "Eco-friendly...mentioning
confidence: 53%
“…The relative abundance of Devosia, another Gram− bacterium, was also increased in the HM samples, with members of this taxon known to tolerate brackish conditions [70]. Devosia can be associated with green algae which is consistent with its increased abundance as the chl a levels increased 3.4-fold, serving as a diazotroph by fixing nitrogen, but it can also facilitate the maintenance of ion homeostasis, which may be significant in the mixed salts of the "eco-friendly" de-icer [71,72]. Since members of Devosia can be halophilic and this genus was found at the highest relative abundance in the HM samples, we cannot exclude that it too was a contaminant in the M de-icer formulation.…”
Section: Shifts In Microbiota At High Concentrations Of "Eco-friendly...mentioning
confidence: 53%
“…Studies have concluded that germination index, vigor index, and seedling fresh weight can be used as effective indicators for screening salt tolerance in oilseed rape at the germination stage [26]. Some scholars have found that sorghum seed shoot length, root length, germination potential, and germination rate showed a sequential decrease with increasing salt concentration and different degrees of delayed germination [27]. The results of the present study were similar to it; with increasing salt concentration germination index and vigor index continued to decline, and the average germination time increased, inhibiting the vigor of oilseed rape seeds and weakening the germination ability (Figure 1).…”
Section: Discussionmentioning
confidence: 99%